EFEK MODERASI LOCUS OF CONTROL PADA HUBUNGAN OTORITAS ATASAN DAN KECURANGAN AKUNTANSI - Bawa, Agus Artha; Yasa, Gerianta Wirawan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The purpose of this study is to obtain evidence between individuals who have an internal locus of control and external locus of control to commit fraud, in both with or without the authority of superiors to commint fraud and using experiment 2x2 factorial design to prove those objectives. The population in this study are Pejabat Pelaksana Teknis Kegiatan (PPTK) on Tabanan Regency Government. This study indicate, that the condition there were authority  delegated from superior to commit fraud, tend to influence individual to act unethically. It also shows, that relation between the authority of superior to fraud becomes higher in individuals who have external locus of control with  authority of superiors to commint fraud condition and relation between the authority of superior to fraud becomes lower in individuals with internal locus of control, when there is no authority of superiors to commint fraud condition.
Keywords: Fraud, Authority Superior, Locus of Control